DIGITAL READING AND VOCABULARY DEVELOPMENT THROUGH LEARNING MANAGEMENT SYSTEM: A REVIEW OF INDONESIAN EFL STUDIES IN THE POST-PANDEMIC ERA - Muhammad Andrie Bagia; Dwita Laksmita Rachmawati (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
ABSTRACT The COVID-19 pandemic accelerated the adoption of Learning Management Systems (LMS) in English as a Foreign Language (EFL) instruction in Indonesia, and this practice has continued into the post-pandemic phase, particularly in the development of digital reading skills and vocabulary acquisition. This study aims to systematically examine empirical findings concerning the effectiveness of LMS in the Indonesian EFL context. The method employed was a systematic literature review following the PRISMA framework, analyzing twenty articles published between 2021 and 2025 through stages of identification, screening, eligibility assessment, and inclusion based on criteria requiring empirical studies focused on LMS use in Indonesian EFL settings and reporting data on reading or vocabulary outcomes. The data were analyzed using qualitative thematic synthesis to identify dominant patterns of findings. The results indicate that LMS expands access to authentic texts, enhances learning flexibility, and facilitates repeated exposure, contributing to improvements in reading comprehension and vocabulary mastery, particularly when combined with explicit tasks such as structured quizzes and digital glossaries. Its effectiveness is influenced by self-regulation, digital literacy, and the quality of instructional design. Conceptually, this review underscores the importance of integrating Self-Regulated Learning, managing Cognitive Load, and applying blended learning approaches as foundational principles for strengthening LMS-based EFL instructional design. ABSTRAK Pandemi COVID-19 mempercepat adopsi Learning Management System (LMS) dalam pembelajaran Bahasa Inggris sebagai Bahasa Asing (EFL) di Indonesia dan praktik tersebut berlanjut pada fase pascapandemi, khususnya dalam pengembangan keterampilan membaca digital dan penguasaan kosakata. Penelitian ini bertujuan mengkaji secara sistematis temuan empiris terkait efektivitas LMS dalam konteks EFL Indonesia. Metode yang digunakan adalah systematic literature review dengan kerangka PRISMA terhadap dua puluh artikel terbitan 2021–2025 melalui tahapan identifikasi, penyaringan, uji kelayakan, dan inklusi berdasarkan kriteria artikel empiris, berfokus pada LMS dalam EFL Indonesia, serta melaporkan data membaca atau kosakata. Data dianalisis menggunakan sintesis tematik kualitatif untuk mengidentifikasi pola temuan utama. Hasil menunjukkan bahwa LMS memperluas akses teks autentik, meningkatkan fleksibilitas belajar, serta mendukung paparan berulang yang berdampak pada peningkatan pemahaman bacaan dan kosakata, terutama ketika disertai tugas eksplisit seperti kuis dan glosarium digital. Efektivitasnya dipengaruhi oleh regulasi diri, literasi digital, dan kualitas desain instruksional. Secara konseptual, kajian ini menegaskan pentingnya integrasi Self-Regulated Learning, pengelolaan Cognitive Load, dan pendekatan blended learning sebagai fondasi penguatan desain pembelajaran EFL berbasis LMS.